Method of tests on an abrasive wear on the chart of Brinell - Hovart (Br - Hv). Part II. Practical realization of method - Кузьменко, А.Г.; Вишневский, О.А. (Problems of Tribology, 2014)
Method of tests on an abrasive wear on the chart of Brinell - Hovart (Br - Hv). Part II. Practical realization of method